Emerging roles of prominin-1 (CD133) in the dynamics of plasma membrane architecture and cell signaling pathways in health and disease - Pleskač, Petr; Fargeas, Christine A; Veselska, Renata; Corbeil, Denis; Skoda, Jan (Cellular & molecular biology letters, 2024)
Prominin-1 (CD133) is a cholesterol-binding membrane glycoprotein selectively associated with highly curved and prominent membrane structures. It is widely recognized as an antigenic marker of stem cells and cancer stem cells and is frequently used to isolate them from biological and clinical samples. Recent progress in understanding various aspects of CD133 biology in different cell types has revealed the involvement of CD133 in the architecture and dynamics of plasma membrane protrusions, such as microvilli and cilia, including the release of extracellular vesicles, as well as in various signaling pathways, which may be regulated in part by posttranslational modifications of CD133 and its interactions with a variety of proteins and lipids. Hence, CD133 appears to be a master regulator of cell signaling as its engagement in PI3K/Akt, Src-FAK, Wnt/β-catenin, TGF-β/Smad and MAPK/ERK pathways may explain its broad action in many cellular processes, including cell proliferation, differentiation, and migration or intercellular communication. Here, we summarize early studies on CD133, as they are essential to grasp its novel features, and describe recent evidence demonstrating that this unique molecule is involved in membrane dynamics and molecular signaling that affects various facets of tissue homeostasis and cancer development. We hope this review will provide an informative resource for future efforts to elucidate the details of CD133's molecular function in health and disease.
Keywords: fosfatidylinositol-3-kinasy; Cilium; CD133; AC133 Antigen; Cell signaling; Cancer stem cell; Microvillus; Neoplastic Stem Cells; Cancer; signální transdukce; Phosphatidylinositol 3-Kinases; Stem cell; Signal Transduction; Cell Membrane; Exosome; buněčná membrána; Lipid raft; nádorové kmenové buňky; Prominin-1; antigen AC133